2011
DOI: 10.1002/ajmg.b.31206
|View full text |Cite
|
Sign up to set email alerts
|

Novel pathogenic mutations and copy number variations in the VPS13A Gene in patients with chorea‐acanthocytosis

Abstract: Chorea-acanthocytosis (ChAc) is a rare autosomal recessive neurodegenerative disorder caused by loss of function mutations in the vacuolar protein sorting 13 homolog A (VPS13A) gene that encodes chorein. It is characterized by adult-onset chorea, peripheral acanthocytes, and neuropsychiatric symptoms. In the present study, we performed a comprehensive mutation screen, including sequencing and copy number variation (CNV) analysis, of the VPS13A gene in ChAc patients. All 73 exons and flanking regions of VPS13A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
60
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 23 publications
3
60
0
2
Order By: Relevance
“…This finding reveals key adaptive changes that participated in the genetic makeup of each equine species, with functions involved in cellular interactions (DSG1, NCAN, TBC1D2) and trafficking (MYO5C, ZW10), metabolism (ACCS, SLC9A4, HMGCR), development (SEMA5A, FAT2), olfaction (BPIFB4), and immunity (ITIH4, SIGLEC1). Interestingly, mountain zebras showed positive selection signatures at VPS13A, a gene associated with locomotory and behavioral disorders (23,24), possibly in relation to their high sociability. The antiporter SLC9A4, involved in pH regulation and countering of adverse environmental conditions, was found to be positively selected in plains zebras, which experience a wide range of environments throughout their geographical range.…”
Section: Resultsmentioning
confidence: 99%
“…This finding reveals key adaptive changes that participated in the genetic makeup of each equine species, with functions involved in cellular interactions (DSG1, NCAN, TBC1D2) and trafficking (MYO5C, ZW10), metabolism (ACCS, SLC9A4, HMGCR), development (SEMA5A, FAT2), olfaction (BPIFB4), and immunity (ITIH4, SIGLEC1). Interestingly, mountain zebras showed positive selection signatures at VPS13A, a gene associated with locomotory and behavioral disorders (23,24), possibly in relation to their high sociability. The antiporter SLC9A4, involved in pH regulation and countering of adverse environmental conditions, was found to be positively selected in plains zebras, which experience a wide range of environments throughout their geographical range.…”
Section: Resultsmentioning
confidence: 99%
“…1 Concerning a pedigree with chorea-acanthocytosis in our previous reports, 1,[3][4][5]8 we would like to correct genetics materials associated with our pedigree already revised by Tomiyasu et al 7 In addition to a heterozygous splice site mutation (8035GϾA, transcript variant A [GenBank NM_033305.2]), which we had reported as 8295GϾA (using a different accession number) in the VPS13A genes of the patients (III-2 and III-3), we identified a novel nonsense mutation (1305GϾA, W435X) in the genes of the unaffected mother (II-4) and patients III-2 and III-3. 7 According to them, the inheritance pattern of the pedigree is actually autosomal recessive (pseudodominant).…”
mentioning
confidence: 98%
“…1 In their Correction, 1 Saiki et al mention with regret that "an error in sequencing occurred and the inheritance pattern should have been reported as autosomal recessive," with no reference to the recent publication of the full details of the mutations in this family. 7 This Correction effectively changes the impact of the original article and, even more so, its title message. We feel that it would be appropriate to retract the 2003 paper in order to reduce further confusion in the literature.…”
mentioning
confidence: 99%
“…Tomiyasu et al 7 noted that the proband reported by Saiki et al is indeed compound heterozygous for mutations in the VPS13A (CHAC ) gene and, therefore, a typical recessive ChAc case. Subsequent to the publication of this report, we found the Correction only via PubMed but missed the original Correction in Neurology.…”
mentioning
confidence: 99%